Systematic Review of Post-Traumatic Parkinsonism, an Emerging Parkinsonian Disorder Among Survivors of Traumatic Brain Injury - Catherine Rojvirat; Gabriel R. Arismendi; Erin Feinstein; Maynard Guzman; Bruce A. Citron; Vedad Delic (Neurotrauma Reports)
This systematic review focuses on an increasing subset of traumatic brain injury (TBI) survivors who develop post-traumatic parkinsonism (PTP), characterized by slowness of movement (bradykinesia), rigidity (stiffness), postural instability, and resting tremors caused by obstruction or damage to deep brain structures of the basal ganglia. PTP is rare, and one hypothesis to explain PTP rarity is that TBIs severe enough to affect deep brain structures are often lethal; however, with increasing survivability of TBIs, these numbers are expected to increase. The goal of this review is to raise awareness of an expected global increase of a subgroup of TBI patients who are treatment responsive and report therapeutic results aiding providers in diagnosing, educating, and treating PTP patients. Literature over the past 100 years was considered, and 44,663 peer-reviewed articles were identified. Inclusion criteria required a clinical indication of parkinsonian signs and TBI. Twenty-six case reports were ultimately included from which 36 individual patient data points were extracted for this review. Between 1980 and 2010, there has been an increase in reporting of PTP decade after decade. Forty-seven percent of PTP cases have 1–6 months of latency to symptom onset, and 83% of cases were male. PTP can occur with or without presence of brain lesions, and the most common type of injuries that cause PTP are motor vehicle accidents followed by falls. PTP patients are responsive to surgery or medication treatments. Further detail on PTP symptomology, treatment responsiveness, and injury types is provided.